2003
DOI: 10.1017/s0952836903003832
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of coalition formation and spatial association in a social carnivore, the African wild dog (Lycaon pictus)

Abstract: In many social species, relationships within groups seem to be non-random but related to variables such as rank, kinship or sexual attractiveness. The endangered African wild dog Lycaon pictus is a social carnivore that lives in large, stable packs, and intra-pack associations might be expected to display similar patterns. We investigated patterns of coalition formation (support during dominance interactions, and partnership interactions) and resting associations between members of a captive pack of 19 wild do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 44 publications
0
62
1
Order By: Relevance
“…Another study using a Bayesian approach provided strong evidence that alpha male turnover would not have occurred in the absence of coalitions in three populations of chimpanzees (Hasegawa & Kutsukake, in press). Outside the primates, one study reported that the beta and gamma males exchanged coalitionary support in African wild dogs (de Villiers et al, 2003). It was inferred that this revolutionary alliance may have enabled the beta and gamma males to overthrow the alpha male.…”
Section: Improving Dominance Rankmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study using a Bayesian approach provided strong evidence that alpha male turnover would not have occurred in the absence of coalitions in three populations of chimpanzees (Hasegawa & Kutsukake, in press). Outside the primates, one study reported that the beta and gamma males exchanged coalitionary support in African wild dogs (de Villiers et al, 2003). It was inferred that this revolutionary alliance may have enabled the beta and gamma males to overthrow the alpha male.…”
Section: Improving Dominance Rankmentioning
confidence: 99%
“…Age effects are not restricted to primates, but have also been documented in other mammals. For example, in a captive group of wild dogs, members of the same age cohort supported each other more than individuals of dissimilar ages (de Villiers et al, 2003). In addition to reinforcing the existing dominance hierarchy, male age-mates may have another important reason to form coalitions when they disperse together and attempt to establish their own breeding groups (de Villiers et al, 2003).…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Of course it should be noted that many real populations are more complex, with group membership in a state of flux, or coalitions between group-mates (e.g. close relatives) ( [14], [46]), and so often our idealised conditions will not apply.…”
Section: Discussionmentioning
confidence: 99%
“…However, helpers offspring are less likely to survive to one year of age than the breeders offspring are and breeder females have been observed to kill helpers pups (Girman et al, 1997). Although the overall level of successful helper reproduction is unclear it is likely that at least some helpers have direct reproduction in the presence of a dominant breeder (Frame et al, 1979;Creel et al, 1997;Girman et al, 1997;de Villiers et al, 2003).…”
Section: African Wild Dog Lycaon Pictusmentioning
confidence: 99%